Analisis aktivitas radionuklida alam dan dosis paparan radiasi pada material bangunan - Riana Anis Safitri; Evi Setiawati; Gede Sutresna Wijaya (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
Building materials cement, gipsum and sand were analized quantitatively and qualitatively for the natural radionuclides using gamma spectroscopy method with detector high purity germanium (HPGe). The highest value observed in the activity concentration of 226Ra, 232Th and 40K were found in sand that 42,12 Bq kg-1, 27,79 Bq kg-1and 316,20 Bq kg-1. The highest value of radium equivalent (Raeq) 106,21 Bq kg-1 was found in sand are bellow the internationally accepted values (370 Bq kg-1). The highest value of internal and external hazard indices were found in sand 0,401 dan 0,287 are less than unity (Hin≤1 and Hex≤1). The highest value of absorbed dose rate was found in sand 49,52 nGy h-1 are lower than the world population-weight average of 84 nGy h-1. The highest annual effective dose values was found in sand 0,243 mSv y-1 is lower than the limit of accepted value 1 mSv y-1. The study shows that measured radioactivity for bulding materials cement, gipsum and sand does not pose as significant source radiological hazard and is save for use in construction of building or dwelling.Keywords: Nature radionuclide, Radiation dose, Gamma spectrometry